38 Association between thalamic atrophy and depression history in an Alzheimer's disease clinical cohort. Issue 12 (14th November 2022) - Loreto, Flavia; Mills, Regan; Duvnjak, Aleksandar; Hakeem, Haneen; Fitzgerald, Anna; Patel, Neva; Win, Zarni; Perry, Richard; Malhotra, Paresh
Abstract : Objectives: We recently found that approximately 50% patients referred for clinical amyloid PET imaging (API) have a history of depressive symptoms (Loreto et al. AAIC2021). Recent studies in selected research cohorts have reported negative associations between left thalamic volume and both disease severity and neuropsychiatric symptoms in Alzheimer's disease (AD) (Low et al. 2019). Here, we performed whole-brain analysis in a clinical patient cohort with confirmed AD and examined the associations between the volume of 8 pre-specified regions (Karavasilis et al. 2017), depression history and amyloid pathology. Methods: We included 69 amyloid-positive (Aβ+) patients seen at the Imperial Memory Clinic between 2013 and 2021, referred for API following appropriate use criteria (Johnson et al. 2013) and given a clinical diagnosis of AD. All patients had an MRI within 12 months of API. Depression history information was collected through structured review of clinical records. Patients were categorised as 'Aβ+D+' (n=32) or 'Aβ+D-' (n=37) based on the presence or absence of a history of depressive symptoms respectively. A control group (Aβ-D-) consisted of 28 cognitively normal amyloid-negative individuals without history of depression. Brain volumes were extracted from T1 images using FreeSurfer and the output was visually checked for segmentation errors. Results: The three groups were comparable for gender, total intracranial volume (TIV), and age, except for the Aβ-D- group which had a higher mean age than the Aβ+D+ group (table 1). We compared the volumes of 8 brain regions across the three groups, controlling for age, gender and TIV. There was an association between 'group' and 'volume' for 7 regions (table 1). Of these, bilateral thalamic volume was the only one to differentiate Aβ+D+ (p=.016) but not Aβ+D- patients from controls, suggesting possible specificity for depression; Aβ+D+ patients had lower mean volume than Aβ+D- although not reaching significance (p=1.00).Analysis of lateralized data revealed significant differences in the left (F [2, 91] = 6.26, p=.003) but not the right thalamus, with lower volumes in both the Aβ+D- (p=.032) and the Aβ+D+ (p=.003) groups compared to Controls. Conclusions: In a real-life clinical cohort, we found evidence of bilateral thalamic atrophy in patients with AD plus history of depression, whereas both AD groups showed reduced volume of the left thalamus. Our results support the clinical relevance of asymmetrical thalamic atrophy in AD pathophysiology and suggest that comorbid depression may exacerbate thalamic volume loss.